Evaluation of Homoeopathic Drugs against Sclerotium rolfsii Sacc. in Groundnut (Arachis hypogea L.) - Sagar, B. Vidya; Basha, S. Ameer; Begum, A. Sajeli; Kumar, K. Ashok; Manchanda, Raj Kumar; Khurana, Anil; Sarangi, Manas Ranjan; Narula, Ritika (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted from June to October, 2022 at the Department of Plant Pathology, College of Agriculture, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad, India to screen the thirty homeopathic drugs under in-vitro condition against the groundnut stem rot pathogen Sclerotium rolfsii. Bio-efficacy of homeopathic drugs was tested by agar well diffusion method to identify the potential drug against stem rot pathogen. In this method, notably, Chelidonium (88.88%) and Colchicum (82.21%) emerged as particularly potent, significantly inhibiting Sclerotium rolfsii mycelial growth and reducing sclerotial formation compared to the control, while Acidium phosphoricum showed a very low mycelial inhibition percentage (13.33%). Chelidonium exhibited the lowest sclerotia production (52), followed by Colchicum (62), compared to the control (400). Sclerotial initiation delayed in Arnica montana (18 days) and Thuja occidentalis (14 days), whereas in the control group, it occurred within six days. Early ooze formation from sclerotia was observed in treatments with Cina and Nux vomica (8 days), while it was delayed in Arnica montana (18 days). The cultural characteristics, such as mycelial pattern, sclerotial arrangement, and color of sclerotia, also changed among the treatments. Significant inhibition of sclerotial germination was observed, particularly with Chelidonium and Colchicum treatments at 15 and 20-minute durations. Chelidonium and Colchicum, shown significant antifungal properties against the groundnut stem rot pathogen. These findings suggest that, homeopathic drugs could potentially be used to manage stem rot in groundnut crop, reducing the reliance on chemical fungicides.